2014
DOI: 10.1177/1362480614557307
|View full text |Cite
|
Sign up to set email alerts
|

Bad jobs and good workers: The hiring of ex-prisoners in a segmented economy

Abstract: Scholarship focusing on barriers to the employment of ex-prisoners has paid little attention to the linkages between mass incarceration and the structural conditions of low wage labor. In contrast, this article considers how decisions to hire ex-prisoners occur in the context of a highly segregated labor market. The research is based upon interviews with employers who are willing to hire persons exiting prisons. These employers were queried about their motivations for hiring, perceptions of their employees wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Indeed, scholars have found that employer aversion does not apply to “dirty work,” and in some cases, employers prefer to hire stigmatized applicants for “bad” jobs (Pager et al., ; Waldinger & Lichter, ). These findings reinforce the need in future research to distinguish among positions and capture not only functionally different job requirements but also status distinctions that render positions more or less suited to hiring stigmatized workers (Bumiller, ).…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, scholars have found that employer aversion does not apply to “dirty work,” and in some cases, employers prefer to hire stigmatized applicants for “bad” jobs (Pager et al., ; Waldinger & Lichter, ). These findings reinforce the need in future research to distinguish among positions and capture not only functionally different job requirements but also status distinctions that render positions more or less suited to hiring stigmatized workers (Bumiller, ).…”
Section: Discussionsupporting
confidence: 62%
“…Some findings also suggest that employers react less favorably to violent convictions relative to other crime types (Holzer, Raphael, and Stoll, ; Husley, ; Pager, ). Even in undesirable employment settings with traditionally high turnover rates, where employers often support hiring people with criminal records in an attempt to find “a good worker to do a bad job,” the findings from a recent qualitative study involving interviews with two dozen employers reveal that violent criminal records may be especially undesirable to employers (Bumiller, ). Most employers are laypersons placed, temporarily or otherwise, in a particular decision‐making context.…”
Section: Study 2: the Mark Of Violence And Contextualization Of Stigmamentioning
confidence: 99%
“…Work-related conditions and programs, moreover, often are understood as eforts to obtain the benefits of employment despite the barriers associated with reentry. The question raised, however, is the balance between expanding access to better forms of work versus leaving barriers intact while pressuring people into whatever "bad jobs" (Bumiller 2015) are available to, or created for, people with convictions.…”
mentioning
confidence: 99%